Vertebral column resection and homogeneous spinal-shortening axial decompression for tethered cord syndrome: a meta-analysis and meta regression - Wardhana, Dewa P. W.; Djojoseputro, Robert E.; Ciaves, Angela F.; Sutedja, Jane C.; Liyis, Bryan G. D. (Frontiers in Surgery, 2025)
IntroductionTethered cord syndrome (TCS) is a group of neurological symptoms due to increased tension along the spinal cord. Surgical untethering has been the conventional treatment to relieve the spinal cord tension. However, untethering is associated with retethering of the spinal cord and the concerns regarding intradural nerve components manipulation. Recently, spinal column shortening (SCS) is emerging as an alternative treatment. This study aims to compare the efficacy of vertebral column resection (VCR) and homogeneous spinal-shortening axial decompression (HSAD) in improving neurological outcomes in TCS and the associated complications.MethodsA PROSPERO-registered systematic search was conducted in the ScienceDirect, PubMed, Embase, and Cochrane databases to identify longitudinal studies up to August 2024 (CRD42024566861). SCS techniques assessed includes VCR and HSAD. Data were extracted on patient demographics, clinical improvements, and complication rates. Single-arm outcomes were pooled using a random-effects GLMM with a logit link. Heterogeneity was assessed and potential moderators were examined through meta-regression. Freeman-Tukey method was used for sensitivity analyses. Publication bias was assessed using Egger's regression test and trim-and-fill analysis. All analyses were conducted with STATA software (p < 0.05).ResultsThe meta-analysis included 15 studies comprising 251 participants (44.2% male; mean age 28.37 ± 5.7 years), with mean operation time of 309.98 ± 53.35 min, estimated blood loss of 1,074.36 ± 338.51 mL, and follow-up duration of 36.95 ± 6.83 months. HSAD had shorter operation time (p = 0.01) and lower EBL (p = 0.04) compared to VCR. Both techniques yielded great improvement in pain, motor and sensory function, bowel and bladder function. HSAD produced significantly greater bladder function improvement compared to VCR (82% vs. 51%, p < 0.001). Complication rate was lower in HSAD compared to VCR (7% vs. 17%), with borderline statistical significance (p = 0.05). Meta regression analyses supported the statistical robustness, especially for pain and bladder function improvement with a constant p-value of 0.03 and 0.02, respectively.ConclusionsVCR and HSAD both offer significant neurological improvements and satisfactory patient outcomes with no comparable significant complications. HSAD has the greater potential to improve bladder function in TCS. Patient treatment selection should be individualized depending on the presence of comorbidity and surgeon's experience.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024566861, identifier CRD42024566861.